Presbyopia compensation: looking for cortical predictors. Issue 2 (22nd April 2016) - Imbeau, Léa; Majzoub, Sadi; Thillay, Alix; Bonnet-Brilhault, Frederique; Pisella, Pierre-Jean; Batty, Magali
Abstract : Background/aims: New surgical techniques have recently been developed in order to compensate for visual impairment and to improve visual comfort for patients with presbyopia. However, the results are still variable, depending on the correction modality used and/or the patient. The main purpose of this study was to identify predictive electrophysiological markers of postcorrection visual comfort for patients with presbyopia. Methods: Thirteen patients with presbyopia (aged between 45 and 60 years) received successive randomised presbyopia compensation with contact lenses supplying monovision (one eye corrected for distance, the other for near vision) and simultaneous vision (progressive lenses). The period for each type of correction lasted for 3 weeks, with a 2-week break without any presbyopia compensation between the two test phases. Examinations were performed at entry (T0) and after each correction modality (Tmono and Tsimult). They included testing for near and distance visual acuity, stereoacuity, binocular contrast sensitivity and electrophysiological recordings (monocular and binocular visual evoked potentials). Results: Follow-up showed no significant differences between the two compensation modalities for either clinical or electrophysiological criteria. However, a significant correlation was found between the difference in TNO score (monovision–simultaneous vision) and the P100 latency evoked by the binocular pattern at T0, suggesting that late P100 latency could be associated with a lesser degree of decrease in stereoacuity with monovision. Conclusions: While our findings do not permit decisions regarding the superiority of one type of compensation over another, these preliminary results support using the P100 latency evoked by binocular patterns as a predictor of postcompensation stereoacuity. Trial registration number: NCT02444130, Pre-results.